Phylogenetic relationships of Heterotrigona itama in Malaysia based on COI DNA sequences - Nur Syafika Mohd-Yusof,; Nik Abdul Rahman Nik-Rashidi,; Nadiatur Akmar Zulkifli,; Salmah Yaakop,; Izfa Riza Hazmi,; Badrul Munir Md-Zain, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
In Malaysia, stingless bee Heterotrigona itama is one of the bee species that is actively reared and mostly utilized in meliponiculture practice. In this preliminary study, we described the phylogenetic relationship scenario among selected localities of H. itama in Peninsular Malaysia and Borneo. Genomic DNA from 16 samples of five localities in Peninsular Malaysia (Kedah, Kelantan, Melaka and Johor) and Borneo (Sarawak) was successfully extracted and sequenced for phylogenetic analysis. The 489 bp mitochondrial DNA of COI sequences was generated for phylogenetic tree reconstruction and population genetic analysis. Tree topology indicated two monophyletic clades which belong to Peninsular Malaysia and Sarawak specimens with high bootstrap support. Five population genetic parameters were studied including nucleotide diversity (π), net nucleotide divergence (Da), nucleotide subdivision (Nst), population subdivision (FST) and gene flow (Nm). The Sarawak samples had the highest scores for all five parameters indicating its genetic affinity to the population in Peninsular Malaysia. Haplotype analysis showed that Kedah-Kelantan samples shared the same haplotype while Sarawak samples had its own unique haplotype with no sharing of haplotypes between other localities. Minimum-Spanning Network generated a visual representation of the relationship reflect a clear separation between Sarawak and Peninsular Malaysia stingless bees samples. This preliminary study shows the importance of understanding the systematic data towards conservation efforts of Malaysian stingless bee’s diversity.